2017
DOI: 10.1016/j.bpj.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

High Tensile Strength of Engineered β-Solenoid Fibrils via Sonication and Pulling

Abstract: We present estimates of ultimate tensile strength (UTS) for two engineered β-solenoid protein mutant fibril structures (spruce budworm and Rhagium inquisitor antifreeze proteins) derived from sonication-based measurements and from force pulling molecular dynamics simulations, both in water. Sonication experiments generate limiting scissioned fibrils with a well-defined length-to-width correlation for the mutant spruce budworm protein and the resultant UTS estimate is 0.66 ± 0.08 GPa. For fibrils formed from en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…In addition, nanomechanical measurements and molecular dynamics simulations provided evidence that mechanical properties of the synthetic filaments, e.g. ultimate tensile strength and Young's modulus, were similar to the corresponding values for other β-sheet materials including amyloids and spider silk (Peng et al ., 2017 a ). These results suggested that β-solenoid assemblies present attractive targets for rational design of novel nanomaterials.…”
Section: Tandem Repeat Assembliesmentioning
confidence: 99%
“…In addition, nanomechanical measurements and molecular dynamics simulations provided evidence that mechanical properties of the synthetic filaments, e.g. ultimate tensile strength and Young's modulus, were similar to the corresponding values for other β-sheet materials including amyloids and spider silk (Peng et al ., 2017 a ). These results suggested that β-solenoid assemblies present attractive targets for rational design of novel nanomaterials.…”
Section: Tandem Repeat Assembliesmentioning
confidence: 99%
“…On one hand, AFM in contact mode has been used to provoke the mechanical deformation of fibrils obtaining the Young’s modulus (here denoted as Y T ) [3032]. On the other hand, the experimental determination of the tensile Young’s modulus ( Y L ) is nontrivial at the nanoscale [33], due to the requirement of a different experimental setup, namely, the more involved sonification method [34]. Moreover, the experimental calculation of the shear modulus ( S ) can be realised by suspending the fibril between two beams and pressing the free part against the indenter, which gives rise to the fibril bending modulus ( Y b ) that depends on both Y T and S .…”
Section: Introductionmentioning
confidence: 99%
“…Two of the designed BSPs (SBAFP and RiAFP) were shown to have tensile strengths similar to those of spider silk and Kevlar. [51] Compared to DNA scaffolds, BSP scaffolds have more chemical functionality and lend themselves better to industrial production. Compared to viral scaffolds, BSP scaffolds offer greater precision of functional group placement and "engineerability" into higher dimensional structures.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration that these two proteins can be used to create amyloid fibrils conjugated with AuNPs is an important step toward creating programmable and functional nanoscale scaffolds with high stability and tensile strength. [50,51] Additionally, both wildtype proteins used as the basis for the design of RiAFP and SBAFP-CT are non-amyloidogenic proteins, proving it is possible using simple design concepts to create fibril-based materials systematically. [41] Materials and methods…”
Section: Introductionmentioning
confidence: 99%